Public policy’s analysis in urban areas : public action in St. Louis (Senegal) against "urbanization at risk" - Coly, Adrien; Sall, Fatimatou (CLACSO, 2021)
Fluvial and oceanic town located in the Sahel, St. Louis is an example of a city which faces to a many uncertainties and presents itself as an area of multiform vulnerability. Built in 1659, it is distinguished by a particular form of urbanization on a site characterized by the ubiquity of water. Urbanization is the result of demographic growth which stimulated an extension of the urban fabric. Analysis of appropriations` practices of space involved by the people in a difficult space shows improper installation in low areas, muddy and wet by the "adventurers the earth" (Coly and Sall., 2014). The process at work in the slums of St. Louis translates a form of "urban risk" on a precarious site. It is responsible of people` exposure to risks and determines a level of vulnerability sustained